41st Structures, Structural Dynamics, and Materials Conference and Exhibit 2000
DOI: 10.2514/6.2000-1695
|View full text |Cite
|
Sign up to set email alerts
|

Fin buffeting features of an early F-22 model

Abstract: Fin buffeting is an aeroelastic phenomenon encountered by high performance aircraft, especially those with twin vertical tails that must operate at high angles of attack. This buffeting is a concern from fatigue and inspection points of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The vortexes over such configurations are well known to contribute to excess lift. The breakdown of those vortex has been the primary cause of severe tail buffeting on the F‐18 E/F (Anthony and Robert, 2005; Moses and Huttsell, 2000; Erickson et al , 1989), and similar behavior has been observed on the F‐22 (Robert, 1999). Due to the similitude in configuration the water tunnel experiment was set up to investigate the vortex breakdown behavior and its relative location to the fin.…”
Section: Water Tunnel Testingmentioning
confidence: 78%
“…The vortexes over such configurations are well known to contribute to excess lift. The breakdown of those vortex has been the primary cause of severe tail buffeting on the F‐18 E/F (Anthony and Robert, 2005; Moses and Huttsell, 2000; Erickson et al , 1989), and similar behavior has been observed on the F‐22 (Robert, 1999). Due to the similitude in configuration the water tunnel experiment was set up to investigate the vortex breakdown behavior and its relative location to the fin.…”
Section: Water Tunnel Testingmentioning
confidence: 78%
“…Wentz (1987), Ferman et al (1990), Zimmerman et al (1989), Shah (1991), Lee & Tang (1992), Martin & Thompson (1991) and Lee et al (1993) characterized the surface pressure spectra on tails of model F/A-18 aircraft. Moses & Huttsell (2000) performed similar types of measurements on the "n of a model F-22 aircraft. Luber et al (1996) assessed the impact of dynamic loads on the design of aircraft.…”
Section: Buffeting Of Tails and Plates: Surface Loadingmentioning
confidence: 99%
“…Studies of model F-18 aircraft, which primarily focused on the surface pressure spectra on tails ( ns), include the works of Wentz, 8 Ferman et al, 9 Zimmerman et al, 10 Shah, 11 Lee and Tang, 12 Martin and Thompson, 13 and Lee et al 14 Similar types of measurements on the n of a model F-22 aircraft were undertaken by Moses and Huttsell. 15 Luber et al 16 addressed the role of dynamic loads on the design of aircraft. Use of active control techniques applied directly to the surface of a n can effectively attenuate the buffet response, as demonstrated by Ashley et al 17 Of course, the origin of buffeting of any aerodynamic surface is the unsteady ow adjacent to it.…”
Section: Introductionmentioning
confidence: 99%